Pengaruh Kinerja Keuangan, Struktur Modal dan Tax Planning Terhadap Nilai Perusahaan - Fatimah, Dewi; Endah Finatariani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to test and prove the effect of financial performance (ROA), capital structure (DER), and tax planning (ETR) on firm value (PBV). This type of research uses a quantitative approach. The population in this study is properties & real estate companies listed on the Indonesia Stock Exchange in 2019-2023, which is 92 companies. Sampling using a purposive sampling method and obtained a sample of 11 companies, so the number of data obtained with an observation period of 5 years is 55 data. The data analysis technique used in this study is panel data regression processed through Eviews 12. The results of this study indicate that financial performance (ROA) does not affect firm value (PBV) and tax planning (ETR) does not affect firm value (PBV) while capital structure (DER) does affect firm value. Based on the results of the F test, the effect of financial performance (ROA), capital structure (DER), and tax planning (ETR) on firm value (PBV) is acceptable, resulting in a regression model that is suitable for use in this study as a basis for decision making.